THE EFFECT OF VARIATION OF SOAKING TIME AND ROLL DISTANCE ON TWO-ROLL BASED MELINJO OUTER SKIN PEELING MACHINE - Yoga Derby Pratama; Bernardus Crisanto Putra Mbulu; Harsa Dhani (Mechanical, Energy and Material (METAL), 2025)
The peeling of melinjo skin is an essential process in melinjo processing to produce higher-value processed products, such as melinjo chips and other food ingredients. Melinjo is a plant commonly found in Indonesia and is used in traditional cuisine and snack production. This study examines the effect of variations in roll distance and soaking time on melinjo fruit. The roll distance variations used were 0.9 cm, 1 cm, and 1.1 cm, while the soaking times were 1 hour, 1.5 hours, and 2 hours. In this study, friction force and compression force from the roll drive played a crucial role in achieving optimal peeling. The friction force is influenced by the roll distance, where a 0.9 cm roll distance generates a high friction force, which can damage the seeds. Conversely, a 1.1 cm roll distance reduces the friction force, making the peeling process less effective. Based on force calculations, the required compression force of the roll drive was 39.22 N. Additionally, the highest friction force was recorded at a 0.9 cm roll distance, reaching 84.76 N, while at a 1 cm roll distance, the result was greater than or equal to the compression force of the roll drive 54,16 N. Meanwhile, at a 1.1 cm roll distance, the friction force was lower than the compression force of the roll drive 23,54 N. The soaking process affects the texture of the melinjo skin. With a 1-hour soaking time, the melinjo seed skin remained relatively hard. At 1.5 hours of soaking, the skin started to soften but still required a significant friction force for peeling. After 2 hours of soaking, the skin became soft, allowing it to be peeled off completely. Based on the data obtained, the best peeling results were achieved at a roll distance of 1 cm with a soaking time of 2 hours, as the skin could be easily removed due to the applied friction and compression forces from the roll drive.